Pengaruh Kualitas Produk dan Brand Image Terhadap Keputusan Pembelian Produk Skincare Skintific (Studi Pada Pengguna Skintific di Samarinda) - Desi Puspita Sari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the simultaneous or partial influence of product quality and brand image variables on purchasing decisions and which of these variables has a dominant influence on purchasing decisions for skintific skincare in samarinda. This type of quantitative research was used in this research by collecting data using questionnaires, interview, observation and documentation. The sample for this research is consumers using skintific in samarinda totaling 100 respondents. Multiple linear regression is the analytical tool used in this research. The research results show that product quality and brand image simultaneously and partially have a significant influence on purchasing decisions and brand image is the dominant variable in purchasing decisions for skintific skincare in samarinda.